Analisis dan Perancangan Sistem Informasi Persediaan, Pembelian, dan Penjualan pada Toko Sinar Jaya - Wawan Saputra (Bina Nusantara University, 2010)
Increased sales and business systems development is a main beam that moves Toko Sinar Jaya on sales of goods primary to secondary to achieving progress in its business. The purpose of this paper is to analyze the potential of information systems strategy implementation and also to develop information systems at Toko Sinar Jaya and to design an application system based on an analysis of existing systems. The research methodology used is the method of analysis and design methods, in which the analysis method used consisted of literature study method, field surveys, and interviews of business processes that are running, whereas in the method of design using object-oriented design and design analysis. Result to be achieved is to provide facilities such as applications that are useful for recording data inventory, purchasing, and sales for Toko Sinar Jaya.